EPIDERMODYSPLASIA VERRUCIFORMIS ASSOCIATED WITH LOW-RISK HPV – A CASE REPORT - Vukovska, Rebeka; Duma, Silvija; Pljakoska, Vesna; Dimitrov, Goran; Dohceva Karajovanov, Ivana; Mircevska Arsovska, Elena (Journal of Morphological Sciences; Vol 6 No 1 (2023): JMS, 2023)
Epidermodysplasia verruciformis (EV) is a hereditary skin disorder that affects the body's ability to eliminate and protect against certain types of human papillomavirus (HPV), resulting in a higher risk of abnormal tissue growth and skin cancer. Typically, the signs and symptoms of this condition are presented during childhood and may include flat warts, macules that resemble pityriasis versicolor, or lesions resembling seborrheic keratoses. An 11-year-old female patient came for examination with viral verrucae that first appeared at the age of 4, on the forehead and hairline. The consulted dermatologist diagnosed verruca plana and proposed local treatment with a topical retinoid (adapalene), with limited efficacy. Over time, the verrucae spread to other areas and the patient received various treatments including cryotherapy, CO2 fractional laser, and several topical creams and oral medications. Due to suspicion of Epidermodysplasia Verruciformis (EV), a skin biopsy was performed. The histopathological findings suggested the presence of Epidermodysplasia verruciformis. The immunological analyses showed the presence of antibodies IgE and IgG At to Ebstein Barr Virus (EBV), and Cytomegalovirus (CMV). A DNA sample was taken from the patient with a biopsy and skin smear, which was subjected to HPV amplification in real-time PCR. Low-risk HPV types 6 and 44 were detected. High-risk HPV was not found. The patient was subsequently given 3 doses of the 9-valent HPV vaccine. Although some improvement was observed in certain areas, new verrucae appeared elsewhere. Patients with EV require frequent check-ups with dermatologists to evaluate for the development of new lesions and malignant transformation. Keywords: Human papillomavirus (HPV), genetic dermatologic condition, autosomal recessive inheritance, cutaneous dysplasia. https://doi.org/10.55302/JMS2361017v